A Mild Case of Adult-Onset Keratosis Lichenoides Chronica Successfully Treated with Narrow-Band UVB Monotherapy - Takashi Nomura; Eiko Toichi; Yoshiki Miyachi; Kenji Kabashima (Karger Publishers, 2012)
Keratosis lichenoides chronica (KLC) is a rare keratotic disorder of unknown origin. Effective treatment has not been established yet. Here, we present adult-onset KLC, which was treated by narrow-band ultraviolet B (NB-UVB) monotherapy. Although NB-UVB was reported to be effective for pediatric-onset KLC, it has not been clear if this regimen is also useful for adult-onset type because pediatric-onset KLC is suggested to be different in nature. We assume that KLC is treatable by NB-UVB regardless of the age of the patient.